Boron-Silicon Film Chemical Vapor Deposition Using Boron Trichloride, Dichlorosilane and Monomethylsilane Gases. (16th June 2021) - Muroi, Mitsuko; Otani, Mana; Habuka, Hitoshi
Abstract : A boron-silicon film was formed by chemical vapor deposition at 800 °C and atmospheric pressure using boron trichloride, dichlorosilane and monomethylsilane gases. With the increasing boron trichloride gas flow rate at the fixed dichlorosilane gas flow rate, the deposition rate and the boron concentration decreased and saturated, respectively, following the rate theory assuming the Langmuir-type model. The obtained film was amorphous and dense without any voids. The monomethylsilane and the silicon hydrides, produced by the thermal decomposition of the monomethylsilane gas, were considered to help decomposing the intermediate boron species at the surface. The boron concentrations of 20%–40%, significantly greater than the solubility in the crystalline silicon, were concluded to be obtained using the boron trichloride gas.